Clinical faculty associates serving as hybrid teacher educators: Personal and professional impacts - Hall-Kenyon, Kendra M.; Smith, Leigh K.; Erickson, Lynnette B.; Mendenhall, Melissa P.; Tingey, Patricia; Crossley, Heather; Runolfson, Janna (Frontiers in Education, 2022)
Background: University supervisors in teacher education assume a complex and demanding role, which is essential to the development of prospective teachers, but is often underappreciated or ignored. Aim: This descriptive study was designed to explore former clinical faculty associates’ (CFAs’) perceptions of the challenges and opportunities inherent in their work as CFAs, and the influence of this experience on their future professional work. Method: Using survey research methodology, followed by selected individual interviews, this paper focuses on the experiences of CFAs, highly respected PK-6 teachers employed by the university for 2-3 years to serve as university supervisors. Results and Conclusions: Although participants reported facing several professional and personal challenges as CFAs, they also described opportunities to participate in a wide variety of professional experiences that positively impacted their future work. Furthermore, most reported feeling the CFA experience was professionally renewing and brought opportunities to build strong personal and professional relationships that cross institutional boundaries.